Вплив деформації молекули Н2О на девіацію хімічного зв’язку О−Н - Yushko, O.O.; Okhrimenko, B.A. (Publishing house "Academperiodika", 2012)
A deviation loop is plotted in the harmonic approximation of molecular vibrations. The loop acts as a sensitive indicator reacting to the initial deformation of a water molecule due to the displacement of H atom from its equilibrium position. The deformation of the molecule leads to a displacement of the secondhydrogen atom. The dependence of the corresponding Lagrangian on the orientation of the coordination plane has been determined.